2018
DOI: 10.1155/2018/5891963
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Effects of Nano/SBR Polymer on Rutting Performance of Binder and Asphalt Mixture

Abstract: Rutting is one of the most common distresses in flexible pavements and can affect vehicle controlling features. Although asphalt binder constitutes a small percentage of the asphalt mixture, its properties play a crucial role in pavement performance and its rutting resistance. One way of improving binder properties and rutting resistance is to use additives. In this research, nanoclay and SBR polymer have been simultaneously used to modify 60–70 penetration binder to study rutting resistance of binder and asph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…OBC for unmodified sample was 4.38% while for 1% and 3% CNT-modified samples it was 4.42% and 4.47%, respectively. Researchers have experienced both increases and decreases in the optimum binder content requirements when utilizing nanomaterials [35,36]. In this study, an increase in optimum binder content was experienced with the increase in CNT dosage.…”
Section: Permanent Deformation Analysismentioning
confidence: 79%
“…OBC for unmodified sample was 4.38% while for 1% and 3% CNT-modified samples it was 4.42% and 4.47%, respectively. Researchers have experienced both increases and decreases in the optimum binder content requirements when utilizing nanomaterials [35,36]. In this study, an increase in optimum binder content was experienced with the increase in CNT dosage.…”
Section: Permanent Deformation Analysismentioning
confidence: 79%
“…7,8 showed that modifying asphalt binder with SBR/WNCP nanocomposites increases rutting resistance that implies a more viscoelastic behavior and more stiffness than that of control asphalt. This trend is mainly due to the fine intercalation and penetration of WNCP into SBR matrix structure [34]. Also, it was noticed that blend 30 exhibited the highest rutting resistance that may be due to the high stiffness of WNCP.…”
Section: Rheological Properties Of Modified Asphaltmentioning
confidence: 94%
“…Increased elasticity, higher adhesion and cohesion qualities of the binders, and a lower rate of oxidation are all benefits of using SBR in mixes (Roque, Birgisson, Tia, Kim & Cui, 2004), this revealed why SBR has been widely used as an important asphalt modifier. Many studies show the addition of polymer (SBR) considered one of the asphalt improvement solutions techniques has been used in several countries (Sadhu & Bhowmick, 2004;Chakraborty et al, 2010;Zhang & Yu, 2010;Ameri, Vamegh, Rooholamini & Haddadi, 2018). These researchers discovered that SBR modified asphalt mixtures could produce exceptional pavement performance, including anti-rutting, anti-cracking, and moisture resistance, which was even better than SBS modified asphalt mixtures (Ren et al, 2018).…”
Section: Introductionmentioning
confidence: 99%